Issues in human security in Asia - Yang Razali Kassim (Strategic currents, 2011)
This volume focuses on the theme of Human Security -- a phenomenon increasingly in the news in Asia. The issues revolve around the security of the individual as opposed to the security of the state. They encompass some of the latest developments affecting or having implications for the well-being of the Asian individual since January 2010. Among them are Japan's triple calamity; Wikileaks; the Arab uprisings; and the death of Osama bin Laden. Issues discussed range from climate change and natural disasters; energy security; health, food, and water security to issues of internal challenges such as governance, politics and identity. The role of diplomacy in non-traditional security, as the larger conceptual framework within which human security resides, is also covered. This is the third volume of Strategic Currents, which publishes essays and commentaries first written for RSIS by scholars, academics and associates of the S. Rajaratnam School of International Studies (RSIS), Nanyang Technological University